MicroRNA-378 Targets the Myogenic Repressor MyoR during Myoblast Differentiation - Gagan, Jeffrey (American Society for Biochemistry and Molecular Biology, 2011)
MicroRNAs play important roles in many cell processes, including the differentiation process in several different lineages. For example, microRNAs can promote differentiation by repressing negative regulators of transcriptional activity. These regulated transcription factors can further up-regulate levels of the microRNA in a feed-forward mechanism. Here we show that MyoD up-regulates miR-378 during myogenic differentiation in C2C12 cells. ChIP and high throughput sequencing analysis shows that MyoD binds in close proximity to the miR-378 gene and causes both transactivation and chromatin remodeling. Overexpression of miR-378 increases the transcriptional activity of MyoD, in part by repressing an antagonist, MyoR. The 3′ untranslated region of MyoR contains a direct binding site for miR-378. The presence of this binding site significantly reduces the ability of MyoR to prevent the MyoD-driven transdifferentiation of fibroblasts. MyoR and miR-378 were anticorrelated during cardiotoxin-induced adult muscle regeneration in mice. Taken together, this shows a feed-forward loop where MyoD indirectly down-regulates MyoR via miR-378.